Abundance, occurrence, and degradation of airborne antibiotic resistance genes in coastal and marine atmospheres - Shijie Jia; Shijie Jia; Xiaohong Yao; Jianhua Qi; Jianhua Qi; Xiaohuan Liu; Xiaohuan Liu; Huiwang Gao; Huiwang Gao (Frontiers in Marine Science)
Antibiotic resistance genes (ARGs) may have significant impacts on human health and ecosystems. Airborne ARGs are reportedly widely distributed across inland cities, but little is known about their abundance in marine atmospheres. Here, we report observations of ambient ARGs during a cruise over the marginal seas of the Bohai Sea and Yellow Sea and compare them with ARGs in the coastal atmosphere. We characterized the ARGs in terms of their abundance, occurrence, degradation, and risk in the marine and coastal atmospheres. Using Na+ and Ca2+ as indicators of marine and continental aerosol sources, respectively, we quantified the mutual transport of airborne ARGs. Our results revealed that the airborne ARG abundances and the number of ARG types increased concomitantly with the mass concentrations of particulate matter because of the accumulation effect, but the ratios of ARG abundance/particulate matter concentration gradually decreased. The inconsistent trend suggested that the reduction in airborne ARGs was greater than their increase with bacterial reproduction during their accumulation and transport in the atmosphere. In addition, the number of ARG types in marine aerosols was greater than that in coastal aerosols. However, the airborne ARG abundance in marine aerosols was greater than that in clean coastal aerosols but not in polluted coastal aerosols. Some ARG types detected in marine aerosols were significantly and positively correlated with wind speed and relative humidity, implying that they may be derived from marine emissions, whereas the other ARGs are likely derived from long-range continental transport. Sea-derived airborne ARGs serve as important sources in coastal aerosols, but their contributions decrease with increasing air pollution levels. Our findings highlight the complex role of marine aerosols as both potential sources and reservoirs of airborne ARGs and highlight the critical importance of investigating the transport dynamics and variation mechanism during the long-range transport of ARGs.